2013
DOI: 10.1038/mp.2013.163
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for greater amphetamine-induced dopamine release in pathological gambling: a positron emission tomography study with [11C]-(+)-PHNO

Abstract: Drug addiction has been associated with deficits in mesostriatal dopamine (DA) function, but whether this state extends to behavioral addictions such as pathological gambling (PG) is unclear. Here we used positron emission tomography and the D3 receptor-preferring radioligand [(11)C]-(+)-PHNO during a dual-scan protocol to investigate DA release in response to oral amphetamine in pathological gamblers (n=12) and healthy controls (n=11). In contrast with human neuroimaging findings in drug addiction, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
117
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(140 citation statements)
references
References 75 publications
17
117
1
2
Order By: Relevance
“…For instance, in contrast to studies in cocaine and alcohol addiction, [ 11 C]raclopride and [ 11 C]‐(+)‐PHNO PET revealed no differences in dopamine receptor DRD2/3 availability and greater stimulant‐induced dopamine release in individuals with GD compared with healthy volunteers (HV; Albein‐Urios et al 2012a,2012b; Boileau et al 2013; Boileau et al 2014). A key modulator of the dopaminergic system is the mu opioid receptor (MOR), and opiate receptor antagonists have some efficacy in treating GD.…”
Section: Introductionmentioning
confidence: 75%
“…For instance, in contrast to studies in cocaine and alcohol addiction, [ 11 C]raclopride and [ 11 C]‐(+)‐PHNO PET revealed no differences in dopamine receptor DRD2/3 availability and greater stimulant‐induced dopamine release in individuals with GD compared with healthy volunteers (HV; Albein‐Urios et al 2012a,2012b; Boileau et al 2013; Boileau et al 2014). A key modulator of the dopaminergic system is the mu opioid receptor (MOR), and opiate receptor antagonists have some efficacy in treating GD.…”
Section: Introductionmentioning
confidence: 75%
“…In particular, PET studies have shown enhanced amphetamine-and gambling-induced dopamine release in the striatum of individuals with pathological gambling symptoms, as compared with healthy controls (Boileau et al, 2014;Steeves et al, 2009). Dopamine D3 receptor binding in the substantia nigra was also shown to be positively correlated with gambling severity (Boileau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with healthy controls, individuals with pathological gambling also exhibit greater DA release (54%-63%) in the striatum and midbrain in response to an oral amphetamine challenge. 14 Using locomotor activity following a low dose of amphetamine as a noninvasive, indirect correlate of mesolimbic DA sensitization, recent studies have shown that repeated expos ure to unpredictable reward delivery 15 or responding for reinforcement on a variable schedule of reward delivery enhanced amphetamine's ability to increase locomotor activity compared with control groups. As a result, both repeated exposure to psychostimulants and uncertainty expos ure (UE) appear to induce a similar behavioural response that likely reflects DA sensitization.…”
Section: Introductionmentioning
confidence: 99%